Learners’ Intrigue and Attitude Towards Presenting Self-Documentaries Technique in Speaking Skill (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aims to probe the students’ intrigue towards presenting self-documentaries technique in learning speaking skills and to probe the students’ attitudes towards presenting self-documentaries techniques in improving students’ speaking skill. This research was a survey research design using observation and questionnaires to get data. To find out the students’ responses regarding intrigues, researcher gave seven questionnaires; interesting technique, exciting topic, enthusiastic, relax, self-confidence, actively in the class, and students’ impression to presenting self-documentaries technique, and to find out the students’ attitudes responses, there were ten questionnaires given to the students. They were a trend technique that can improve students speaking skill, easy technique to improve students’ spoken, improve students fluency, improve students accuracy, improve students vocabulary, feeling confidence, getting many ideas, easy to express ideas in speaking, improve students’ curiosity about the topic of speaking, giving students ideas to increase their speaking through using social media. The data showed that 83.79 % agreed, and 16.20% disagreed. It mean that the positive response of intrigues percentage was higher. Students were immensely intrigued by the topic, and students was very interested in learning English in the class through Presenting Self-Documentaries Technique. Response to the students’ attitudes was that 78.32 % agreed, and 21.68 disagreed. It means that students positively react to the Presenting Self-Documentaries Technique in increasing their speaking skills. Based on the data above, students have more significant positive responses. The Presenting Self-Documentaries Technique is interesting in learning the speaking skill, and it is an effective technique to increase students’ speaking skills. Presenting self-documentaries designs can motivate students to learn English autonomously to improve students’ speaking skills significantly.
Keywords: Attitudes; Intrigues; Speaking Skill; Presenting Self-Documentaries